Assessing the atmospheric oscillations effects on the biology of the bullet tuna (Auxis rochei) and its possible linkage with global warming - Nuñoz Expósito, Pedro (2015)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve; Instituto Español de Oceanografia; 2015 This study aims to explore a possible effect of the atmospheric oscillations on the physical condition and the variability in landings of the bullet tuna (Auxis rochei), as well as to provide further information about the biology of this highly migratory species, which is under an increasing commercial pressure. In order to accomplish to accomplish these objectives a total of 2381 individuals of A. rochei were collected all over the Spanish Mediterranean coast. Each individual was measured, weight, sexed and aged. The fitness condition indexes (Kmean and LeCren) were posteriorly obtained individually after the representation of the length-weight relationships. Additionally, fisheries and atmospheric oscillations data were also obtained. A non-parametric Spearman test (α=0.01) was used to correlate the atmospheric oscillation indexes with both physical condition indexes and annual landings data. Finally, a Mann-Whitney test (α=0.05) was used to test significant differences between the physical condition of males and females for both the pre-spawning and post-spawning individuals. The results obtained reflect that the atmospheric oscillations, indexed by the North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO), associated to a time lag (between six months and one year) between the prevalence of the atmospheric conditions and the biological responses in the individuals. Generally, positive phases of the NAO index (negative AO) enhance the migration towards the Mediterranean Sea (higher Kmean), and positive phases of AO (negative NAO) favor the exit towards the Atlantic Ocean (higher LeCren index). These results are explained by the modification of the predominant winds that could favor the migration, as well the nutrients availability after the spawning period. It was also observed that the condition factor in females is significantly larger than in males, ...